A Study of ELE Students’ Perception of Undiksha Moodle E-learning in Pedagogical Courses - Ni Luh Putu Viranicka Septyani; I.G.A Lokita Purnamika; Nyoman Karina Wedhanti (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
E-learning has significantly influenced the educational field. Education currently utilizes e-learning as one of the learning systems that facilitate students and teachers' learning process is distanced or traditional, or even in blended learning. One of the platforms used is the Undiksha Moodle E-learning Platform used in the pedagogical courses. This study aimed to identify students' perception of the use of the Undiksha Moodle E-learning platform. This discussion focuses on the effectiveness offered in the use of the Undiksha Moodle E-learning platform. This study is a case study involving 15 English Language Education students. This study's object is students' perception of using the Undiksha Moodle E-learning platform in the pedagogical courses. Data collections were done with questionnaires and semi-structured interviews to see the suitability of perceptions expressed by students. Data analysis is conducted qualitatively supported with quantitative data by considering the questionnaires' results and interpreting the data obtained. This study showed that English Language Education students have a positive perception of using Undiksha Moodle E-learning. The findings on the effectiveness of the use of the Undiksha Moodle E-learning platform used amounted to 4,173. That indicates that students strongly agree that the platform is effectively used in pedagogical courses.